TRANSFORMASI DUNIA PENDIDIKAN DI SEKOLAH DASAR DALAM MASA PANDEMI COVID-19 - Pamungkas, Dyan Eka; Sukarman, Sukarman (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2020)
ABSTRACTThe temporary closure of educational institutions to withstand the spread of the Covid-19 pandemic around the world has affected millions of students, especially the education system in Indonesia. The Covid-19 pandemic forced the world's people to define the meaning of life, the purpose of learning and the nature of humanity. In education, COVID-19 has drastically changed the learning model; all learning activities are conducted online ranging from elementary school to college level. This research aims to describe the utilization of online learning models in the learning process in elementary schools. The data obtained in the form of qualitative data containing a description of the results of learning observations and teacher interviews on the utilization of online learning models in elementary schools. The research was conducted at SDN Sambirejo III Nganjuk. Based on the results of the interview, online learning activities at SDN Sambirejo III have been effective by utilizing the Classroom Group Whatss app, Google Classroom, and Zoom. The problem in the implementation of online learning is the problem of internet connection that is less supportive.Keyword: COVID-19, transformation, online learning ABSTRAK                                                                                          Penutupan sementara lembaga pendidikan untuk menahan penyebaran pandemic Covid-19 di seluruh dunia telah mempengaruhi jutaan siswa, terutama sistem pendidikan di Indonesia. Pandemi Covid-19 memaksa masyarakat dunia mendefinisikan makna hidup, tujuan pembelajaran dan hakikat kemanusiaan. Dalam bidang pendidikan, COVID-19 telah mengubah model pembelajaran secara drastis; seluruh kegiatan pembelajaran dilakukan secara online mulai dari tingkat sekolah dasar sampai perguruan tinggi. Penelitian ini bertujuan untuk mendeskripsikan pemanfaatan model pembelajaran daring dalam proses pembelajaran di Sekolah Dasar. Data yang diperoleh berupa data kualitatif yang berisi deskripsi tentang hasil observasi pembelajaran dan wawancara guru mengenai pemanfaatan model pembelajaran daring di sekolah dasar. Penelitian dilaksanakan di SDN Sambirejo III Nganjuk. Berdasarkan hasil wawancara, kegiatan pembelajaran dengan mode daring di SDN Sambirejo III sudah efektif dengan memanfaatkan aplikasi Whatss Grup kelas, Google Classroom, dan Zoom. Kendala dalam pelaksanaan pembelajaran daring yaitu masalah koneksi internet yang kurang mendukung.Kata Kunci: COVID-19, Transformasi, Pembelajaran Online